GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 649836074 species occurrences available in GBIF matching the query: All data. The dataset includes 649836074 records from 13759 constituent datasets: 194 records from Bodenteicher Seewiesen. 61 records from Wälder im Hainbachtal. 62 records from Lebensraum Dorf. 132 records from Aachtobel. 101 records from Steinbruch Kronungen. 106 records from Antarctic Nemertea. 241 records from UAM Mammal Observations (Arctos). 11926 records from Crispin S. Guppy Collection. 63 records from Stadtbiotop Ulrichteich. 498 records from Riedensee. 154 records from Wildkräuter. 1258 records from CMC_ornithology_GRC. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 468 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 356 records from Morphologische Daten von Puffinus creatopus. 246987 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 1 records from Arthropoden aus südostalpinen Höhlen.. 447 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5549 records from Diplopoda (NSMK-DI). 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 398 records from Tsetse flies of East Africa update. 11806 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 53985 records from BioMar - LIFE project. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 3633 records from Bioimages. 31917 records from Mollusca of Costa Rica (INBio). 8857 records from Artròpodes d'Andorra. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 116410 records from Naturalis Biodiversity Center (NL) - Crustacea. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 6 records from Hemichordata collection of National Museum of Nature and Science. 97 records from DMNH Eggs. 1348 records from Inventory of Wari maro forest (Benin). 15100 records from Northern Ireland Mammal Database. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 6543 records from University of Ghent - Zoology Museum - Vertebratacollectie. 336 records from Macroarthropods, Isua 2013, Greenland. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 10072 records from Guadeloupe_Herbier. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 1 records from Oribates calcaratus. 375 records from Phthiraptera. 58475 records from Oregon State University Herpetological Collection. 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 5 records from Arthropoden aus südostalpinen Höhlen.. 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 215 records from The Diptera Site. 28385 records from Plan de vertebrados de la Patagonia. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 3 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 1 records from Nothrus spinifer. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 159069 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 373 records from Otter survey of Ireland 2004 & 2005. 123 records from Bryozoa of the British Isles. 3105 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 48944 records from Grey seal at-sea distribution 2009-2014. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 10730 records from kpabg_lichens. 156156 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 31 records from Siphonaptera. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 8934780 records from Botanical Society of the British Isles - Vascular Plants Database. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 20 records from Heteroptera - SMNG. 10000 records from National Lesser Horseshoe Bat Database. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 2312 records from Mycological collection of the National Museum. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 3509 records from Entocytheridae (Ostracoda) World Database. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 5796 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 1303 records from Mid Ulster Hare Surveys 2012-2015. 1238 records from Insect Collection (CeStuBio). 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 22311 records from HUEM - Herbário da Universidade Estadual de Maringá. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 67914 records from HUFU - Herbarium Uberlandense. 1030627 records from Phanerogamic Botanical Collections (S). 3 records from MSB Mammal Observations (Arctos). 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 1650 records from University of Calgary Herbarium. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 12161 records from ISE - Herbário ISE. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 167 records from A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 9302 records from Ants from the Paraguayan dry Chaco. 379 records from WNMU Fish Collection (Arctos). 1641 records from NCSM PaleoBotany Collection. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 1485 records from IWDG Constant Effort Cetacean Sighting Scheme. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 14030 records from JOI - Herbário Joinvillea. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 8220356 records from OEH Atlas of NSW Wildlife. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 457 records from Microbial Observatory of the Laboratoire Arago. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 99300 records from Landesmuseum Kärnten. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 12279 records from ISM Mammalogy Collection. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 191 records from Herpetofauna laguna El Tinije. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 13912 records from Fishes in MZNA-VERT: freshwater communities in the Larraun river (Spain). PhD project, Javier Oscoz & Master project, A. Cos.. 20 records from Truchas Mexicanas. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 3 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 59016 records from Biological Records Centre - Isopoda (Interim dataset). 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 3103 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 9349 records from Harriet Irving Botanical Gardens (HIBG). 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1 records from Celaeno plicata. 7735 records from CSUC Vertebrate Collection. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 1 records from Hoplophora globosa. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 9 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 33 records from Revision von Suctobelba trigona (Michael, 1888). 20043 records from Mollusca collection of National Museum of Nature and Science. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 90189 records from African Rodentia. 111784 records from Jordal. 268891 records from MVZ Herp Collection (Arctos). 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1 records from Damaeus concolor. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 5709 records from Coleoptera of Piska Forest. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 115324 records from University of Vienna, Institute for Botany - Herbarium WU. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 170316 records from Australian National Wildlife Collection provider for OZCAM. 1 records from Zetes longiusculus. 3204 records from Faunal Inventory of Morysin Nature Reserve. 184364 records from LACM Entomology Collection. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 60672 records from QLD DERM Coastal Bird Atlas (Trial). 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 7427 records from Weevils of the Tatra Mts.. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 1266 records from Actinomycetes Collection in BCRC. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 712 records from Herbier G. Garapin (BOUM). 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 9889 records from uconn-mammals. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 1 records from Nothrus runcinatus. 1702 records from BioGIS - Bryophytes - HUJ collections. 5826 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 4 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 89874 records from ecoscope_observation_database. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 4343 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 22213 records from Coleção de Aves do Museu Nacional / UFRJ. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 10633 records from Biological Records Centre - Collembola Recording Scheme. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 5 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 16346 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 38652 records from Marine species distributions in Irish coastal waters. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 2546 records from The atlas of butterflies in Kraków. 232734 records from MVZ Mammal Collection (Arctos). 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 8136 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 288 records from Fungi of Słowiński National Park, Poland. 10358 records from Census of the flora of Benin. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 22049 records from Tromsø Museum, Bryophytes. 76 records from Birdrace-Birding_for_Nature-Bonn. 1998 records from Aves de la cuenca media del río Bogotá. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 16685 records from UFG - Herbário da Universidade Federal de Goiás. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 653 records from Colección nacional de palmas de Colombia - JBQ. 50 records from Lindesnes. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 159 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 10075 records from Nematoda of Costa Rica (INBio). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 24 records from Transferred depository for twenty-seven holotypes of the plant bug and flower bug species recently described from Thailand (Hemiptera: Heteroptera: Miridae and Anthocoridae). 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 12 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 412 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 353 records from Coastal and marine species. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 34 records from New records in vascular plants alien to Kyrgyzstan. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 13597 records from Orthopteroidea. 12370 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 859 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí (Antioquia, Colombia). 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 4 records from Fossil (SMNH-FO). 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 4424 records from Portuguese Seaweeds. 3 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 11 records from The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001 (Trichoptera: Hydropsychidae), endemics of Crete (South Aegean, Greece), with notes on their ecology. 4918 records from Otter in coastal areas - Carcasses. 64 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 100 records from Brock University Herbarium (BU). 741967 records from PlutoF platform observations. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 76 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 6 records from Coleção de Tardigrada do Museu Nacional - UFRJ. 1 records from Hoplophora ferruginea. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 1020 records from Irish Marine Turtle Database. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 511 records from Coleoptera of Swierklaniec Forest. 39415 records from Online Atlas of vascular plants 2012-2020. 15637 records from CCBER Herpetology Collection. 52994 records from IAC - Herbário do Instituto Agronômico de Campinas. 9788 records from SANT-Lich. 7 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 561820 records from Bee Biology and Systematics Laboratory. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 8 records from Order Diptera, family Mydidae. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 2007 records from Palaeobiology collection, FAU Erlangen. 2 records from Two New Jumping Spiders of the Genus Chalcoscirtus from China (Araneae: Salticidae). 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 10102 records from Herbarium Vonderau - FULD. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 1 records from Red list project inventory, bryophytes. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 3 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 1 records from Oribates fuscipes. 1196 records from Entomological collection of the National Museum. 22804 records from TCWC Marine Invertebrates. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 1 records from Celaeno obsoleta. 6266 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from Miriapodi di alcune grotte della Campania. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 88901 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 55855 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 9836 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 35325 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 121225 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 7251 records from All Ireland Marsh Fritillary Database. 834 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 26880 records from KUBI Ornithology Tissue Collection. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 28626 records from SANT-Algae. 6237 records from Plecoptera. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 458185 records from Bird Atlas 2007 - 2011. 6381 records from UPRM Invertebrate Collection. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 42659 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 829 records from Colección Hidrobiológica del Chocó. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 5733 records from Small Mammal Research Database. 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 485 records from National Taiwan Ocean University. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 4719911 records from Naturalis Biodiversity Center (NL) - Botany. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 13253 records from CHAS Ornithology. 1 records from Nothrus segnis. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 1 records from Oribates gilvipes. 3503 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 7693 records from NHM, Heteroptera. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 1284 records from Collection of Heteroptera. 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 4579 records from Herbarium WRSL, Flora of the Silesia. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 1419956 records from AntWeb. 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 4686 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 177466 records from CAS Entomology (ENT). 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 2116 records from Collection entomologique Pierre Lachiver. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 259949 records from Zoology (Museum of Evolution - Uppsala). 1 records from Lissotes working-group. 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 389 records from Amphibian and Reptilian (KIEE-AR). 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 1 records from Zetes cespitum. 720 records from Herbarium Senckenbergianum (GLM) - Lichenes. 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 48087 records from SPSF - Herbário Dom Bento José Pickel. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 1124142 records from PRECIS. 1219 records from Dutch Butterfly Monitoring Indexes. 2494 records from Marine Environmental Monitoring - Marine Turtles. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 33070 records from CSIRO Ichthyology provider for OZCAM. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 1201 records from monocotyledonous_geophytes_of_fergana_valley. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 934424 records from Fishbase. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 5194 records from SMNS Palaeontological collection - Amber and fossil insects. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 239 records from Irish Federation of Sea Anglers Catch Data. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 128244 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 130222 records from Occurrence records of southern African aquatic biodiversity. 5331 records from bird. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 25 records from Hyolithen - SMF. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 13094 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 1678 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 6541 records from Likona Invertebrates. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 28788 records from EPA River Biologists data. 190 records from Relative abundance of ostracods in sediment core Sv09. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 5505 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 8 records from Helfer H. 1936. The fishery grounds near Alexandria. VIII Pantopoda. Notes et memoires No 16. 4766 records from Paläontologie Marburg. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 16 records from Taxonomic review of the genus Wasmannia.. 17618 records from BioGIS - Mammals - INPA database. 94696 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 53866 records from SPF - Herbário da Universidade de São Paulo. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 6 records from Collection Myriapoda - SNSD. 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 145959 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 66722 records from SANT herbarium vascular plants collection. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 5 records from First records of Pseudodoros nigricollis Becker (Diptera: Syrphidae) from Cyprus. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 1167 records from Biological Reference Collections ICM CSIC. 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 624 records from Collection of botanical drawings by Georg Schweinfurth at B. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 372 records from Colección de Entomología - Arthropoda. 47558 records from UFP - Herbário UFP - Geraldo Mariz. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 15 records from Projeto Abrace o Boto Cinza. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 3447 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 99 records from French national collection of Solanum tuberosum. 52 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 47499 records from Sphaeroceridae Collection. 1329 records from API_CRSN_Data. 50317 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 24945 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 2513 records from Carabidae of the Tatra Mts.. 166781 records from KUBI Mammalogy Collection. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 444 records from Insect Collection from New Caledonia. 7509 records from Perot Museum of Nature and Science. 654 records from Helgeland Museum, Tabanidae. 1636 records from Mammal Recording Scheme, 1970-85. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 4849 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 88771 records from URM - Herbário Pe. Camille Torrand. 76130 records from University of Alberta Vascular Plant Herbarium (ALTA). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 51181 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 585 records from Ascomycetes of Russian Fennoscandia. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 4447 records from Lepidoptera (Observations). 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 268 records from mcme_uplb_museum_plant_collection. 702 records from HSU Vertebrate Museum Reptile Collection. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 98585 records from LSUMZ Herps Collection. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 19127 records from Biological Records Centre - Cerambycidae Dataset. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 68304 records from IICT Herbário LISC. 85003 records from Herbario Universidad de Antioquia (HUA). 2 records from Note sur les fourmis du Musée Zoologique de l'Académie Impériale des Sciences à St. Pétersbourg.. 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 3182 records from Finnish Entomological Database: Heteroptera. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 612934 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 57306 records from Colección Herbario Federico Medem Bogotá - FMB. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 2011 records from Local BioBlitz Challenge 2013. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 900522 records from FLORIVON. 51969 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 191855 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 409 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 2247562 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 61 records from Registros restauración ecológica- Magdalena medio. 558 records from Mammals in MZNA-VERT: skull and teeth development in Rattus and Mus. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 77 records from Empria and Monsoma in Japan. 99463 records from NPL collections. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 73975 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 660 records from VMNH Invertebrate Paleontology. 387504 records from Species data extracted from the National Vegetation Database. 10606 records from Cercle des mycologues de Montréal Fungarium (CMMF). 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 7671 records from HERBAM - Herbário da Amazônia Meridional. 116610 records from ICN - Herbário do Instituto de Ciências Naturais. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 26835 records from Herbario Pontificia Universidad Javeriana. 2174 records from MLZ Mammal Collection (Arctos). 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 157566 records from Lund Museum of Zoology - Insect collections (MZLU). 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 751 records from Trichoptera (caddisflies) of Ireland. 3 records from Note su alcune specie di chilopodi della regione palestinese. 652 records from Spider species diversity from wet and dry habitats. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 44 records from Solanum_baretiae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 1004 records from National Museum of Marine Biology and Aquarium. 416644 records from Entomology, Natural History Museum, University of Oslo. 255 records from Inventario de Plantas Mámbita. 253105 records from Lyman Entomological Museum (LEMQ). 6855 records from Echinoderm collection of National Museum of Nature and Science. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 13086 records from Collection of Coleoptera. 63 records from (Data S1) Palynology of ODP Site 119-739. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 634257 records from Inventario Español de Especies Terrestres (MAGRAMA). 1 records from On centipedes (Chilopoda) of Albania, 2. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 1 records from Hoplophora decumana. 530 records from Collection Crustacea - KAUMM. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 6258 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 1 records from Oribates flammula. 6817 records from Colección de Reptiles del Instituto Alexander von Humboldt. 110660 records from The avian collection at the Natural History Museum, Oslo, Norway. 2392 records from Fongs d'Andorra. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 1 records from Cepheus latus. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 1 records from Eremaeus hepaticus. 13993 records from Herpetology. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3779762 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 1 records from Pelops torulosus. 173415 records from Hymenoptera specimen database of Kyushu University. 1 records from Oribates picipes. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 3257 records from fundiv france database. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 9054 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 5850 records from UAFMC Fish. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 2082 records from Vietnam Type Culture Collection. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 1 records from Myriopoden von Epirus. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 52 records from Isotope tracer experiment: meiofauna counts. 5053399 records from Southern African Bird Atlas Project. 2576 records from Hosted Invertebrate Collection 01. 7403 records from Fishes in MZNA-VERT: freshwater fishes of Hidalgo state (Mexico). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 16749 records from IMOS - AusCPR: Phytoplankton Abundance. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 365 records from Colección Herpetológica de la Patagonia. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 12512 records from ULg_Hexapoda. 4498 records from Colección Herbario Universidad Católica de Oriente. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 15640 records from The Fish Collection at the Zoologische Staatssammlung München. 377096 records from University of Florida Vertebrate Paleontology. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 374 records from published_chenopodium_vulvaria_observations. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 1746416 records from SA Flora (BDBSA). 80128 records from NCSM Fishes Collection. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 2848 records from Kangawalla Bird Sightings. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 3945 records from TTRS Ornithology. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 1359 records from Polychaetes from two subtidal rocky shores of the North coast of Crete, collected for the NaGISA project 2007-2008. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 2880 records from Coleoptera, NEF. 357405 records from BioFokus. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 127876 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 21704 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 207 records from BioAcoustica: Wildlife Sounds Database. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 155 records from Megophthalmidia_of_North_America. 873 records from Kartlegging av spredning av fremmede bartrær. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 29490 records from Tromsø Museum, Fungi. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 1948 records from CCBER Mammalogy Collection. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 9 records from Cypridinid Ostracods. 99830 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 119366 records from The digitization of plant specimens of NTU. 8164 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 77 records from Xiphosura collection of National Museum of Nature and Science. 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 1481 records from Reptilia notes, NTNU, Trondheim. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 4266 records from UAFMC Birds. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 86556 records from NINA Vanndata øvrige arter. 1 records from A new Garcorops species from Madagascar copal (Araneae: Selenopidae). 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 60344 records from AM: Freshwater Invertebrates (1900-2005). 4660 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 12051 records from ISM Ornithology Collection. 126383 records from UAM Mammal Collection (Arctos). 2481 records from HSU Wildlife Eggs and Nests. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 223433 records from Phytochorologie des départements français. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 4761 records from SMDB - Santa Maria Departamento de Biologia. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 471 records from Aschelminth collection of National Museum of Nature and Science. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 767 records from BioGIS - Bats - Asaf Tsoar database. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 9959 records from UAM Fish Collection (Arctos). 45688 records from DMNS Bird Collection (Arctos). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 81329 records from natagora-earlybirds. 2 records from Arthropoden aus südostalpinen Höhlen.. 3688 records from Clare Biological Records Centre dataset. 12434 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 11 records from Pollen profile from sediment core AV14_K2-4. 2297 records from Joint Nature Conservation Committee - England Otter Survey Database. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 33522 records from Dragonfly Ireland. 25813 records from Amphibian Specimens. 221558 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 355 records from Culture Collection of Cryophilic Algae. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 762 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 32 records from Archaea Collection in BCRC. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 1 records from Zetes rubens. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 582 records from Bioblitz 2013 Copenhagen Denmark. 1 records from Nothrus pollinosus. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 288954 records from Coordinated Waterbird Counts. 9879 records from Bibliographic records of Angola mammals. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 72236 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 255 records from GENT Lactarius Deliciosi. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 26624 records from Monitoring data from the federal state Bavaria (Germany). 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 2654 records from Collection of Hymenoptera. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 397 records from Danish Lacewings (Neuroptera). 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 7 records from Description of Eutetrapha weni n. sp. from Guizhou, China (Coleoptera: Cerambycidae: Lamiinae: Saperdini). 1364 records from Irish Collembola records. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 46 records from Coleção de Nematomorpha do Museu Nacional - UFRJ. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 514 records from SDSM Vertebrate Paleontology Collection. 102 records from Sipuncula collection of National Museum of Nature and Science. 1049 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 588 records from Relative abundance of ostracods in sediment core Lz1120. 1 records from Nothrus pigerrimus. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 156 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 133656 records from NINA insect database. 22041 records from CUMV Mammal Collection (Arctos). 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 6065 records from LISU Herbario Angola. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 1861 records from Banc de Germoplasma Vegetal de les Illes Balears-JBS. 352692 records from Plantae of Costa Rica (INBio). 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 3105 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 3 records from Taxonomic considerations on Lobocneme Rehn, 1911 and Paroxyopsis Rehn, 1911 and a new synonymy (Insecta Mantodea: Stagmatopterinae). 53643 records from CESJ - Herbário Leopoldo Krieger. 58 records from Mamíferos laguna El Tinije. 1952 records from ISM Ichthyology Collection. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 13995 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 51748 records from Museu Paraense Emilio Goeldi - ichthyology Collection. 2856 records from Alien macro-invertebrates in Flanders, Belgium. 1322 records from PSUZC-Amphibians Collection. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Threskiornithidae. 7473 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 13717 records from OUPR - Herbário "Professor José Badini". 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 22137 records from Global compendium of Aedes albopictus occurrence. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 895 records from Lichen.ie Data. 2396 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7208 records from Royal Horticultural Society - Records from the RHS insect reference collection. 1 records from Nothrus bispinosus. 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 2358 records from MISE Project Otter Records, 2011-2015. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 13004 records from HAS-Algae - Coleção Ficológica do HAS. 1 records from Zetes ephippiatus. 34237 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 1 records from Études myrmécologiques en 1886.. 1 records from Zetes fuscomaculatus. 151 records from Molluscan fauna of Gueishan Island of Taiwan. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 820552 records from Fauna Atlas N.T.. 3377 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 7410 records from Helgeland Museum, Lepidoptera. 15879 records from HAMAB - Herbário Amapaense. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 52 records from CIM Specimens. 260 records from SuLaMa reptile survey II 2012. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 109 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 1 records from A new African Apiocera species (Apioceridae, Diptera). 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 90894 records from CUMV Fish Collection (Arctos). 76253 records from Irish Vascular Plant Data - Paul Green. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 99 records from IWDG Ship Surveys Sightings - Heritage Council Surveys 2004. 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 8 records from A new pygmy grasshopper species (Tetrigidae: Tetriginae) from Central India. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 136 records from Plants galls. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 41523350 records from Artdata. 464 records from Lepidoptera collection, NTNU, Trondheim. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 13325 records from Herbier du Bénin. 2577 records from Shellfish (WSHN-MS). 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 9123 records from Flora of Słowiński National Park, Poland. 1 records from Systematics of the bubblegum corals (Cnidaria: Octocorallia: Paragorgiidae) with description of new species from New Zealand and the Eastern Pacific. 2444 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 4 records from Beiträge zur Kenntnis der Spinnenfauna des Kt. Tessin III - Für die Schweiz neue und bemerkenswerte Spinnen (Arachnida: Araneae). 79126 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 519292 records from Museum Victoria provider for OZCAM. 3947 records from The importance of host tree age, size and growth rate as determinants of epiphytic lichen diversity in boreal spruce forest.. 21670 records from Butterflies of Ireland. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 47934 records from CRCM Vertebrate Collection. 3 records from Diatom abundance of Hole 38-338, Part 2. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 3221 records from Road Kill Survey. 19 records from Counts of benthos communities in Kongsfjorden in 2009. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 1826 records from Collection des Mollusques (BOUM). 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 6 records from MfN - Micropaleontology. 711 records from Odonata collection, NTNU, Trondheim. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 2983 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 8579 records from The atlas of breeding birds in Małopolska. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 276513 records from MBM - Herbário do Museu Botânico Municipal. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 382 records from Reptilia ZMK. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 3769 records from Eggs Specimen. 4 records from New genus of diminutive microhylid frogs from Papua New Guinea. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 71 records from (Data S1) Palynology of ODP Site 113-696. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 1905 records from BioGIS - Reptiles - INPA database. 777 records from INRA-Versailles Arabidopsis natural variants. 2412 records from Ohio University Invertebrate Paleontology Collection. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 3420 records from Harvestmen of French Guiana. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 6133 records from FCAB - Herbário Friburguense. 104 records from Mammalogie ZMK. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 18940 records from Cowan Tetrapod Collection - Mammals. 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 6 records from Arthropoden aus südostalpinen Höhlen. 1803 records from Flora of tanzania. 38282 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 13625 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 1323 records from Algae (KBRC-AG). 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 91 records from European bison in Białowieża Primary Forest. 24 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Nothrus canaliculatus. 314 records from Peces laguna El Tinije. 31 records from Coleção de Nemertea do Museu Nacional - UFRJ. 10895 records from Stabbetorp - Floristiske registreringer 2016. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 10255 records from Araneae Collection. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 30 records from Specimens from India at the University Museum at the University of Bergen. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 12876 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 2815 records from Helgeland Museum, Araneae. 527 records from Inventaire floristique de Beza Mahafaly. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 3 records from New Species of Woolly Lemur Avahi (Primates: Lemuriformes) in Bemaraha (Central Western Madagascar). 1664 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 11392 records from Danish Plant Bugs (Miridae). 30129 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 24121 records from Endemic plants of the Congo basin. 2 records from Zobellia amurskyensis sp. nov., Zobellia laminariae sp. nov. and Zobellia russellii sp. nov., novel marine bacteria of the family Flavobacteriaceae. 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 119 records from Various insect orders, NEF. 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 11762 records from Chrysomelidae of the Carpathians. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 882456 records from SA Fauna (BDBSA). 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 10 records from Cnidaria ZMK. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 8805 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 2172 records from Colección de Reptiles. 3 records from Collection Crustacea - ZSRO. 1 records from SDSM Botany and Paleobotany Collections. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 667180 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 1 records from Nothrus bicarinatus. 39 records from Arachnologie ZMK. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 165299 records from CAS Invertebrate Zoology (IZ). 2 records from Porifera ZMK. 12 records from Echinodermata ZMK. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 61 records from Shrews of Poland. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 36048 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 3720 records from Saproxylic Beetles of Ireland. 132 records from Fiocruz/CCAMP - Coleção de Campylobacter. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 1 records from Celaeno spinosa. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 15953 records from Algae (S). 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 16452 records from Fungus herbarium, UiB. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 146809 records from OHN. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 1626 records from Ornithologie ZMK. 159523 records from Lund Museum of Zoology (MZLU). 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 2 records from Amphibia ZMK. 637399 records from Données ONF Faune-Flore-Fonge. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 2 records from Bryozoa ZMK. 27290 records from Bird Monitoring Data. 4 records from Tunicata ZMK. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 20727 records from Arctic Species Trend Index (ASTI) : Terrestrial. 3276500 records from Insecta of Costa Rica (INBio). 62015 records from Atlas of Iberian water beetles (ESACIB database). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 2 records from Description of Hoplolaimus bachlongviensis sp. n. (Nematoda: Hoplolaimidae) from banana soil in Vietnam. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 906 records from Digital Florula - Las Cruces Biological Station. 23562 records from Arctic Species Trend Index (ASTI) : Marine. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 1 records from On the Chilopoda from Turkey. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 411 records from SuLaMa reptile survey I 2012. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 2957 records from HSU Wildlife Mammals. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 1129 records from Upper Silesian Museum, Insect Collection. 370 records from Ichthyologie ZMK. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 1 records from Oribates angulatus. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 1 records from Protozoa ZMK. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 1 records from Oribates badius. 898 records from kyklades. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 1262 records from Crustacea ZMK. 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 657 records from MVZ Hildebrand Collection (Arctos). 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 51 records from Packer Collection / Xenochilicola bees, Chile. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 281 records from Myriapoda of Costa Rica (INBio). 6 records from Vermes ZMK. 1 records from Ctenophora ZMK. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 496203 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 2 records from REDESCRIPTION OF TETRAMORIUM ATLANTE CAGNIANT, 1970, NEW STATUS (HYMENOPTERA: FORMICIDAE: MYRMICINAE). 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 1 records from On the Chilopoda from Turkey. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 2223 records from Colección de Zoología Invertebrados - Otros invertebrados. 5581 records from IWDG Casual Cetacean Sightings. 32109 records from Herbier de Nouvelle-Calédonie. 2 records from Pantopoda SMF. 3 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 6796 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 13 records from Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae). 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1 records from On centipedes (Chilopoda) of Albania, 2. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 38 records from Harant H. 1939. Les fonds de peche pres d'Alexandrie. Ascidiacea (Cartes 1-5). Notes et Memoirs No 28. Institut fouad 1er d' Hydrobiologie et de peche, Egypt. 4 records from New country records of reptiles from Laos. 89 records from Collection Crustacea - PUM. 14420 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 2777 records from Plant (KIWE-PL). 2 records from A review of the ant genus Harpegnathos Jerdon, 1851 (Hymenoptera: Formicidae) in the Philippines, with the description of two new species. 2095 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 68 records from Malakologie ZMK. 16621 records from Crustacea collection of National Museum of Nature and Science. 28 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 1029 records from Freshwater plants of Cameroon. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 1 records from Nothrus convexus. 200 records from Zoological collection of the National Museum. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 1000 records from Colección Limnológica del Chocó. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 377 records from Herbario MAIA, colección de Eucaliptus del INIA-CIFOR. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 37694 records from Tallinn Botanic Garden. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1329 records from Colección de Invertebrados Cenpat (CNP-INV). 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 385 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 1055244 records from Norwegian Biodiversity Information Centre - Other datasets. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 7000 records from CCBER Ornithology Collection. 212157 records from Estonian Museum of Natural History. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 9 records from Chenopodium vulvaria. 11251 records from Herbarium areqvipense (HUSA). 688 records from Algae, Norwegian College of Fishery Science. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 29513 records from MPM Herpetology. 1 records from Die Chilopodenfauna Griechenlands. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 2954 records from Geneva Herbarium – Burnat Herbarium (G-BU). 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 2502 records from ISM Herpetology Collection. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 57401 records from Naturalis Biodiversity Center (NL) - Mammalia. 12542 records from Herbarium of the Université Libre de Bruxelles. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 589 records from Birds (NMNO-BI). 8795 records from HPBR - Herbário Padre Balduino Rambo. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 2224 records from UCM Bird Eggs/Nests Collection (Arctos). 21091 records from NCSM Birds Collection. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 9933 records from CHAS Mammalogy Collection (Arctos). 210019 records from Invert Paleo Specimens. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1415 records from Plant observations from Białowieża National Park. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 2666 records from Insect (JNHM-IN). 163 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 749213 records from Historical Bird Atlas. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 1614 records from Culture Collection of Algae. 28735 records from UAM Bird Collection (Arctos). 144 records from Checklist of Fabaceae Lindley in Balaghat Ranges of Maharashtra, India. 30926 records from Annelida collection of National Museum of Nature and Science. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 111 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 21694 records from arim. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 7551636 records from BirdLife Australia, Birdata. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 8102 records from tef-database. 48 records from Tardigrada collection of National Museum of Nature and Science. 299492 records from SEAPOP NINA. 718 records from HSU Vertebrate Museum Amphibian Collection. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 9948 records from Bees of Canada / Gschwendtner property collection. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 7 records from (Table 4) New palynological record of sediments from Odderade. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 8887 records from The tunicates collection (IT) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1186 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 5658 records from ESAS cetacean sightings from 1980 to 2003.. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 2071933 records from Museum of Comparative Zoology, Harvard University. 6821 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 3117 records from Naturalis National Natural History Museum (NL) – Coelenterata. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 58044 records from Naturalis Biodiversity Center (NL) - Cnidaria. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 1 records from Amycolatopsis marina sp. nov., an actinomycete isolated from an ocean sediment. 5328868 records from Australia's Virtual Herbarium. 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 450 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 38841 records from Herbier de Strasbourg. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 1667138 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 432 records from Plantas Bosque Seco Chicamocha. 1 records from Flora of Suriname, volume VI, part I. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 197759 records from Vascular Plant Herbarium, UiB. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 17 records from Hazel Dormouse in Ireland. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 56302 records from Kathryn Kalmbach Herbarium. 1 records from Nothrus palliatus. 1833 records from Censos navideños de aves y censo neotropical de aves acuáticas en 10 áreas protegidas de Parques Nacionales Naturales de Colombia.. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 15 records from Chenopodium. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 27033 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 6211 records from NMMNH Mammal. 1299 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 163 records from Entomofauna laguna El Tinije. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 823 records from Líquens d'Andorra. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 4852552 records from Bird Ringing Centre in Sweden (NRM). 211883652 records from EOD - eBird Observation Dataset. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 1808 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 197083 records from Ichthyology Collection - Royal Ontario Museum. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 1696 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 21868 records from Fishes in MZNA-VERT: foraging ecology of the kingfisher. PhD project, Antonio Vilches. 6004 records from Colección Limnológica Universidad de Antioquia. 98287 records from CAS Ornithology (ORN). 74 records from SuLaMa reptile monitoring. 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 1 records from Zetes latipes. 6 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 69622 records from Fundación Miguel Lillo - Colección Entomológica. 409 records from Herbario MAIA, colección de Quercus del INIA-CIFOR. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 18900 records from UCBG TAPIR Provider. 1 records from Hypochthonius rufulus. 260950 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 20957 records from CHAS Herpetology. 1 records from Zetes morticinus. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 29171 records from Naturalis Biodiversity Center (NL) - Collembola. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 1910784 records from Consortium of California Herbaria. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 798 records from Biological Records Centre - Irish Otter Dataset. 192907 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 169 records from The Pteridaceae family diversity in Togo. 50128 records from Tasmanian Museum and Art Gallery provider for OZCAM. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 49637 records from Monitoring data from the federal state Hesse (Germany). 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 1022683 records from iNaturalist Research-grade Observations. 154 records from UCM Vertebrate Observations Collection (Arctos). 3 records from A remarkable new species of the genus Lepisiota Santschi (Hymenoptera: Formicidae) from Oman and the United Arab Emirates with a key to the Arabian species. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 6 records from Mammalia (JNHM-MM). 98 records from Colección Nacional de Heliconias. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 70111 records from Kyushu University Museum Coleoptera Collection. 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 3002 records from Colección de Peces Universidad Católica de Oriente. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 807 records from Reunion_Coffea. 25543 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from Neue Milbenarten aus Kärnten. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 3669 records from ARKO strandeng. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 5578 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 9787 records from Finnish Entomological Database: Hymenoptera. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 8629 records from National Taiwan University. 3 records from Mammals (SMNH-MM). 5790 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 21 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 172126 records from CONN. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 30009 records from HUCS - Herbário da Universidade de Caxias do Sul. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 34 records from National System of Protected Areas in Poland - Fungi. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 1 records from Oribates ovatus. 1965 records from Global caridean shrimp fauna. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 3225 records from Aquatic Oligochaeta of Ireland. 558827 records from Aranzadi Ringing Scheme (bird ring-recovery data). 1077 records from BioGIS - Fish - HUJ collections. 1896 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 319 records from HTSAw - Xiloteca do Trópico Semiárido. 30000 records from Birds collection of Yamashina Institute for Ornithology. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 10866 records from Heteroptera of Ireland. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 4498 records from Flora of Japan Specimen Database. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 2 records from A new species of Neossos Malloch (Diptera: Heleomyzidae) from the Yukon Territory, Canada, and a revised key to the Nearctic species. 1 records from Hoplophora crinita. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 50880 records from H.A. Stephens Herbarium. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 2043 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 50000 records from observe_tuna_bycatch_ecoscope. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 70432 records from National Bat Database of Ireland. 1489 records from Herbarium Rhoenmuseum Fladungen. 4 records from A new ant genus from the southwestern United States.. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 8518 records from Upper Silesian Museum, Bird Observations. 13968 records from NYSM Birds. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 352 records from Universidad de Málaga: MGC-Lichen. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 116144 records from Recent Invertebrates Specimens. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 1733 records from Birds collection of Abiko City Museum of Birds. 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 2275 records from UFRN-Fungos - Herbário UFRN - Fungos. 480 records from Spiders of French Guiana. 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 8441 records from Natural England - Batsites inventory for England. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 4829 records from Coleção de Polychaeta do Museu Nacional. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 29 records from A Revision of the Genus Synagelides Strand, 1906 (Araneae, Salticidae) in Korea. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 21749 records from University of Lethbridge Herbarium (LEA). 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 10339 records from KUBI Ichthyology Tissue Collection. 1900 records from Fungi Collection. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 3 records from Salticidae from the Himalayas. The genus Hasarius Simon, 1871 (Araneae: Salticidae). 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cinclidae. 1594 records from Musée Vert ornithology collection. 1 records from Murcia trimaculata. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 221998 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 181 records from Alien Species in Poland - Animals. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 1035 records from National Museum Of Marine Science & Technology. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 4745 records from Collection botanique Le Grand A. (BOUM). 41 records from Shieldbug Records. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 13909 records from AM: Terrestrial Insect Collections (1896-2000). 33173 records from Global Lacustrine Diatoms. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 1752 records from Herbier National de Mauritanie (HNM). 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 850 records from Shellfish (NHMK-MS). 8706 records from NINA botanical collection. 374 records from Macroarthropods, Godthåbsfjorden (Nuup Kangerlua) 2013, Greenland. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 14333 records from DMNS Marine Invertebrate Collection (Arctos). 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 25128 records from rmca-albertine-rift-butterflies. 4 records from A new genus and species of Acaenitini (Hymenoptera, Ichneumonidae, Acaenitinae) from China. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 221963 records from Essig Museum of Entomology. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 18004 records from Census of the animals of Benin. 1 records from On the Chilopoda from Turkey. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 959 records from SMNS Palaeontological collection - Fossil mammals. 64 records from Kabelskebach (Kabelsketal, Saalkreis). 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 11 records from Pollen profile from sediment core AV14_K2-1. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 998 records from minsok. 17 records from Broch H. 1935. The fishery grounds near Alexandria. III Cirripeds. Notes et Memoires No 10.. 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 98 records from acari. 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 2966 records from Bolivian Amazon lowland fish metacommunity data. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 425354 records from University of California Museum of Paleontology. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 86659 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 419514 records from Meadow and Pasture Inventory (SJV). 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 348808 records from Estonian University of Life Sciences. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 1914 records from Macrophytes_CLF. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 1359 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 1031 records from Circumpolar Seabird Monitoring Plan. 43857 records from Mammals housed at MHNG, Geneva. 84521 records from BioGIS - Vascular plants - INPA database. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 1447 records from Odonata of the Congo River 2010 expedition. 1244 records from Mosquitoes_of_French_Guiana. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 79406 records from KUBI Vertebrate Paleontology Collection. 95564 records from ALCB - Herbário Alexandre Leal Costa. 56 records from Onychophora of Costa Rica (INBio). 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 23 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1 records from Zur Kenntnis der Lithobiiden. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 19553 records from Wildbook for Whale Sharks. 10000 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 245 records from Coleção de Platyhelminthes do Museu Nacional - UFRJ. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 6192 records from HUSC - Herbário Unisanta. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 392968 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 131642 records from mel. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 1 records from Nothrus piceus. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 204986 records from CAS Ichthyology (ICH). 10295 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 1 records from Nothrus mutilus. 252060 records from Moths Ireland. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 23215 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 613 records from Countryside Council for Wales - Shad Monitoring data. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 6559545 records from NMNH occurrence DwC-A. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 15813 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 10234 records from Collection entomologique Barthélémy. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 360 records from Order Araneae. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 11 records from Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia.. 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 1189 records from kerkyra. 22031 records from Fishes in MZNA-VERT: baseline freshwater sampling campaigns. 1915 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 10 records from Redescription of the little-known grasshopper Willemsella (Acrididae, Hemiacridinae) from Peninsular Malaysia. 205 records from infish. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 3327 records from BioGIS - Mammals - SPNI. 17447 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 57495 records from TNHC Ichthyology Collection. 100 records from PSUZC-Reptile Collection. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 127 records from Birdrace_Schräge_Vögel-Herford. 88 records from Birdrace-WeserEggeLäufer-Höxter. 241 records from BIRDRACE RennVögel Münsterland. 57 records from Waldhusener Moor (Lübeck-Kücknitz). 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 167 records from Zielbach (Töll). 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 45 records from Flusswerder in der Weser (Hameln). 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 117 records from Wassermann. 28 records from Sandgrube Zaisertshofen. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 35 records from Urwald 3 (Bad Waldsee). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 139 records from NSG Leist bei Ziegenhain. 245 records from Gieselbachtal Fulda-Harmerz. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 39 records from ECOCEAN MantaMatcher. 10 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 1166 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 29264 records from NCSM Vertebrate Paleontology Collection. 15736 records from DMNS Mammal Collection (Arctos). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 5450 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 129 records from Mammalia (KNAM-MM). 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 2413 records from Literature based species occurrence data of birds of North-East India. 110 records from Birdrace-LiLaMai-Vechta. 105 records from Birdrace-ARKONAuten-Rügen. 92 records from Birdrace-Team_BO-bachter-Bochum. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 5549 records from Diplopoda (NSMK-DI). 1659 records from MISE Project Waterford Otter Records, 2011-2015. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 25883 records from Monitoring data from the federal state Saxony (Germany). 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 128 records from Birdrace-Brut-Wetteraukreis. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 120 records from Birdrace-Kosmos_Racer-Freising. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 114 records from Birdrace-Finkenspötter-München. 112 records from Birdrace_Die_Borner-Viersen. 111 records from Birdrace-Uhulogen-Lippe. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 109 records from Birdrace-Team_Charadrius-Günzburg. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 101 records from Birdrace-Herford-Birder-Herford. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Enger_am_Spektiv-Herford. 103 records from Birdrace-Die_Nachtigallen-Herford. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 108 records from Birdrace-TriumVIErat-Viersen. 100 records from Birdrace-Meister_der_Herzen-Kleve. 96 records from Birdrace-federleser-Herford. 95 records from Birdrace-Buteo1_DO-Dortmund. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 85 records from Birdrace-Die_Paradiesvögel-Herford. 72 records from Birdrace-Buteo2DO-Dortmund. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 59 records from Im Bauerngarten. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 185 records from Klasse 3a. 34 records from Borkhart. 114 records from Flora. 100 records from Feriendorf Ober-Seemen. 100 records from Grenzturm Hohen Neuendorf. 5036 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 37 records from Berlin - Treptower Park / Karpfenteich. 44 records from "Schlechteberg" Ebersbach/Sa.. 101 records from Naturgrundstück (Eutin). 69 records from Lassentiner Moor (Niepars). 69 records from Schulgarten mit Klasse 8a (Essen). 97 records from Döchtbühlwald (Bad Waldsee). 84 records from Roter Berg Werdau (Leubnitz). 15 records from AKG-Bensheim. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 282 records from Deponie Klausdorf. 313 records from Stadtpark Herzberg (Elster). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 342 records from Kremmer Luch. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 233 records from Föhrenried (Fronreute und Baindt). 263 records from Artenvielfalt Kreis Gießen. 270 records from Regenrückhaltebecken (Zeulenroda). 20 records from Motzener Tonsee. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 170 records from Bodenseeufer Radolfzell. 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 95 records from Ortelsbruch - Hangmoor bei Morbach. 101 records from Naturhausgarten. 64760 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 107 records from Landschaftsschutzgebiet Buchhorst 3. 63 records from Erft in Selikum (Neuss). 79 records from Balkon (Norderstedt). 99 records from Düne am Ulvenberg (Darmstadt). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 77 records from Trockenrasen Franzigmark (Halle/Saale). 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 172 records from Dalbekschlucht. 2816 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 257 records from Seewasen. 162 records from Siegen/ Gymnasium Am Löhrtor. 360 records from Küstenschutzwald. 198 records from FNL e.V.. 83 records from Spechtwald. 271 records from Beweidungsprojekt an der Nesse. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 80 records from Förderzentrum Schmölln. 122 records from Kloster Eberbach. 97 records from LauWi. 144 records from Ehmkendorf. 70 records from Lech 2001. 151 records from Isarufer. 52 records from Fledermaus. 55 records from Waldsee. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 113 records from Hochschulgelände (Bremen). 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 57 records from Heidesee / Halle. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 245 records from Kiesgruben Wemb. 23 records from Alter Nördlicher Friedhof (München). 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 39 records from Südpark (Bochum-Wattenscheid). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 66 records from Wedeler Au. 56 records from Zitadelle Berlin-Spandau (7b). 54 records from Wiese am Unterbecken. 22 records from Dellwiger Bach (Dortmund). 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 41 records from Örtzemündung (Stedden). 308 records from Wangerooge. 219 records from Umgebung der Grundschule Oderberg. 96 records from Die Wuhle. 149 records from Wirbach. 180 records from Paul-Gerhardt-Schule Dassel. 161 records from Schussenaue bei Berg. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 31 records from Nationalpark Harz Schul-AG Braunlage. 150 records from Steinbruch Mainz-Weisenau. 325 records from Triebesbach (Zeulenroda-Triebes). 36138 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 69 records from "Schwarzes Teich" (Waldpark Radebeul). 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 46 records from Hainbachtal in Oelsnitz/V.. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 145 records from privater Garten. 86 records from Alter Kreidebruch Saßnitz/Rügen. 113 records from Rund um das LUGY. 50 records from Junge Heide, Radebeul/Dresden. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 59 records from Rund ums Ökohaus (Würzburg). 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 103 records from Wasserwerkspark (Chemnitz). 160 records from Wirbach-Taubental (Bad Blankenburg). 48 records from Trockenrasen bei Dörndorf. 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 41 records from Wiese und Bach beim Unterbecken (Markersbach). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 4 records from Arthropoden aus südostalpinen Höhlen.. 65 records from Mauernacker (Wettsaasen). 5 records from Streuobstwiese (Mittelgasse 4). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 99 records from Dorfrand Mauderode. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 153 records from Selztal bei Friesenheim. 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 40 records from Flächennaturdenkmal Grubditz. 61 records from Artenvielfalt auf der Wiese. 43 records from Saalewiesen Naumburg. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 155 records from Bammentaler Duft- und Heilkräutergarten. 58 records from Weidewirtschaft. 85 records from Insektenvielfalt Ahe/Weichelsee. 106 records from Schulgarten Hans-Carossa-Oberschule. 54 records from Ludwigshofen. 122 records from Stever. 71 records from Bolzplatz. 18 records from Spielwiese. 12 records from Kindergarten. 9 records from Willersalpe. 79 records from GymnQuerfurt. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 54 records from Zentralfriedhof (Wien). 73 records from Varnhalt. 18 records from Mittelstreifen. 108 records from Mainufer. 32 records from Schulhof Sandhofenschule (Mannheim). 163 records from Brander Wald (Stolberg). 124 records from Wiesenbiotop am Wasserturm. 181 records from Spießwoogtal / Königsbruch (Fischbach). 212 records from Artenvielfalt im Beckerbruch (Dessau). 1 records from Papilio Sticheli nov. spec. aut subsp.. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 111 records from Ökologischer Weinberg (Guntersblum). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 103 records from Schwanseepark (87645 Schwangau). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 17 records from Schutzgebiet Ochtersum. 22 records from Heilpflanzen im Hainbachtal. 110 records from Obstwiese Osterberg. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 50 records from Artensuche auf den Elbwiesen in Radebeul. 59 records from Oschenberg, NO von Bayreuth-Laineck. 4 records from Schulbiotop und Brigach (Villingen). 98 records from Warnowtal (Rostock). 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 19 records from Goethe-Hauptschule/Projekt I-10. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 60 records from Schafsweide Seniorenhaus Berghof. 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 28 records from Uferzone Wipper (Biesenrode). 22 records from Breitkopfbecken (Berlin-Reinickendorf). 62 records from Amtsrain Apolda-Zottelstedt. 43 records from Schulgelände Thurmair-Gymnasium. 28 records from Hainbachtal bei Oelsnitz / V.. 55 records from Flora und Fauna am Mittelrheintal. 244 records from WildesMoor bei Schwabstedt. 53 records from Weidegut Rechab. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 101 records from Isartal Dingolfing. 147 records from NABU-Auerochsenweide. 92 records from Birkenloh. 94 records from Kochertgraben II. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 63 records from Hochschule Zittau/Görlitz. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 107 records from vegoek. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 207 records from Biosphäre Bliesgau. 69 records from Entdeckertour am Muldestausee 1/05. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 40 records from Öhmdwiesen und Göldern (Konstanz). 54 records from Weidegebiete in der Selzrenaturierung. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 134 records from Birdrace-Team_Havelland-Havelland. 155 records from Birdrace-Usedommeln-Ostvorpommern. 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 128 records from Birdrace_turbine_untersee-Konstanz. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 133 records from Wulfsmuehle/Pinnau. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 95 records from Vielfalt verschiedener Wiesen. 214 records from Binsenwiesen. 98 records from Rund ums Cani. 86 records from Naturerlebnisraum Koppelsberg (Plön). 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 60 records from NABUGEO1. 97 records from Landschaftspark St.Leonhard-Deisendorf. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 13 records from Garten Hamburg Uhlenhorst. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 221 records from Römertal (Steinpleis). 21 records from Riedkanal Bötzingen. 29 records from Naturerfahrung. 51 records from Steinbachtal (Würzburg). 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 51 records from Schrebergarten Düsseldorf Oberkassel. 39 records from Regenrückhaltebecken Bad Bevensen. 21 records from Tauchen und Meer 02. 32 records from Nationalpark Harz Juniorranger. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 23 records from AKG-Gelände in Bensheim. 19 records from Glemstal (Leonberg). 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 48 records from Heider Bergsee (Brühl). 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 719 records from IBF Monitoring of Plant Galls. 3 records from FFR Hausen. 8 records from Krittenhorster Wald (Ostkilver). 1 records from Graureiher in Lans. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 18 records from Naturtag. 15 records from Tiere. 59 records from Schulteich Freie Waldorfschule Darmstadt. 881 records from Moluscos Marinhos de Augusto Nobre. 93 records from Höltigbaum. 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 61 records from GE-Brühl. 47 records from Neanderthal. 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 193 records from Gelände des Schulzentrums am Himmelsbarg. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 10 records from Feuchtwiesen Wippertal bei Wippra. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 172 records from Leben im Finkensteiner Moor. 39 records from Soolbach-Tal. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 53 records from Bad Bodenteicher Heide. 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 57 records from Schulgarten Fichteschule. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 65 records from LSG "Großes Bruch". 48 records from Morphologische Daten von Natrix. 46 records from 8c. 21 records from Bach. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 40 records from Schulhof Liebfrauenschule Oldenburg. 16 records from Im und um das Schulhaus. 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 15 records from Regenwasserabfangsbecken (Erlenbach). 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 5 records from Naturschutzgebiet Ahrmündung (Remagen). 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 122 records from Birdrace-Hügelland-Mainz/Bingen. 100 records from Birdrace-The_Ringers-Friesland. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 79 records from Birdrace-Bielefinken-Bielefeld. 23 records from Wiese Niederaula. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 102 records from Industriebrache (Kempen). 31 records from Kurler Busch (Scharnhorst). 36 records from Selz (Ingelheim am Rhein). 142 records from Kinderbauernhof Pinke-Panke. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 81 records from Stadtpark Schmölln. 87 records from Klütwald. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 49 records from Dörnberg. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 15 records from Die geheimnisvolle Welt der Spinnen. 117 records from Naturschutzgebiet Kochertgraben. 81 records from Schulgarten-St.-Georg-Gymnasium. 26 records from Schulteich Heinrich-Mann-Schule. 20 records from Lerchenauer Baggersee (München). 28 records from Stadtpark Prinzengarten (Sigmaringen). 1 records from Hoplophora ardua. 10 records from schlittschuhweiher. 15 records from Beisetal bei Niederbeisheim. 8 records from Kleiner Ziergarten Winzingen (Neustadt). 20 records from Mikroorganismen. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 23 records from Tümpel Schulbiologiezentrum. 12 records from Kinderwald Hannover. 15 records from Bodentiere rund um die Schule. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 29 records from Insekten. 13 records from FND "Weißer Berg" Leißling. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 42 records from sbosch. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 89 records from Birdrace-Team_Wangerooge-Friesland. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 62 records from Zoo Frankfurt. 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 39 records from Stausee Weiditz. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 47706 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 63 records from Sternwiese Mülheim-Broich. 81 records from Birdrace-Die_Ornithomaten-Herford. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 71 records from Birdrace-do_elster_Dortmund. 78 records from Birdrace-Die_Laufenten-Braunschweig. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 54 records from Park Schönfeld (Kassel). 57 records from Garten in Schmölln. 36 records from Plöwener Wald. 64 records from Schafheide im Böblinger Wald. 10 records from Ökowerk Emden. 64 records from Pilzlehrwald. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 35 records from Gym Freyung. 27 records from Vögel. 101 records from Hoher Stein Kallenhardt. 22 records from Bachabschnitt der Nette (Osnabrück). 141 records from Draubiotop Lavamünd. 70 records from Birds (SMNH-BI). 11 records from Waldgebiet Todtnau- Sonnhalde. 57 records from Mauervegetation,Flechten und anderes. 56 records from Estetal (Buxtehude). 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 64 records from Issumer Fleuth. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 27 records from Zwickau- Schwanenteich. 68 records from Streuobstwiese. 21 records from LBV-Kindergruppen Markt Tussenhausen. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 47 records from Schulgelände Ceciliengymnasium. 31 records from Regenwasserabfangbecken. 4483 records from MVZ Bird Observations (Arctos). 84 records from Streuobstwiese Haus Zeitz. 26 records from Erhard Sopp. 51 records from Mühlenbach bei Buxtehude. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 13 records from Tiere im Teichgebiet. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1174 records from Sudeniederung (Amt Neuhaus). 29 records from Brenz (Heidenheim). 23 records from Ackerrain Plönhagen. 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 27 records from Wiese hinter der Schule (Darmstadt). 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 36 records from Salzwiese Diekskiel. 45 records from Georgs-Padd (Wangerooge). 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 11 records from Privatteich(St.Leon). 40 records from Tiere und Pflanzen um uns herum !. 15 records from Kirchheller Heide ( Bottrop). 12 records from Ohemoor (Hamburg/Norderstedt). 4 records from Sächsische Schweiz (Wehlener Gebiet). 94 records from Landschaftsschutzgebiet Buchhorst 4. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 36 records from Olympiapark (München). 24 records from Ornithologische Wanderung um Tussenhausen. 80 records from Lahnufer in Villmar. 24 records from Kaisertal. 22 records from Kaltenkirchen Brache. 709 records from Upper Silesian Museum, Bird Collection. 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 6 records from Fließgewässeruntersuchung am Haselbach. 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 13 records from Warnowufer Groß Klein. 9 records from Wiesendreieck Luckenwalde. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 5 records from Feuchtwiese. 23 records from Wattuntersuchung (Cuxhaven). 34 records from Wattenmeer-Safari (Wurster Watt). 17 records from Tierpark Zittau. 6 records from Sächsische Schweiz (Pfaffenstein). 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 17 records from Kohlbach (Sulzfeld). 10 records from Bachpatenschaft Beeke. 15 records from Urwald 2 (Bad Waldsee). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 7 records from Stadtrandlandschaft Apolda-Nord. 5 records from Schulinnenhöfe (Gelsenkirchen). 6717 records from LSUMZ Mammal Tissues. 3 records from Blankenfelder See. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Fledermäuse über der Alster (Hamburg). 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 27 records from Bäche im Mooswald (Vörstetten). 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 24 records from Tauchen und Meer. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 1 records from Waldtag in und um Seelingstädt. 4 records from Neues Testprojekt. 163 records from Tiere und Pflanzen am Pfannenbach. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 89 records from Schulgelände Paul-Gerhardt-Schule. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 13 records from Tag der Artenvielfalt am Bruckenwasen. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 61 records from Fürstenberger Ralley Teil 3. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 146 records from LK 11 im Mönchspark. 272 records from BIRDRACE Niederlausitz-Team. 256 records from BIRDRACE Upupa epöpse. 254 records from BIRDRACE Thüringer Becken-Birders. 138 records from BIRDRACE Arkonauten. 157 records from BIRDRACE Rheinische Wasserrallen. 82 records from BIRDRACE Die Ziegeneier. 84 records from BIRDRACE Avinauten. 91 records from BIRDRACE NABU LV Hessen. 98 records from BIRDRACE Die Paradiesvögel. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 102 records from BIRDRACE Willi goes Birding. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 158355 records from All Ireland Non-Marine Molluscan Database. 105 records from BIRDRACE Kiesmätze. 174 records from BIRDRACE Bon(n)apartemöwen. 106 records from BIRDRACE Ave Goettingen!. 134 records from BIRDRACE Griffin Wood Warblers. 132 records from BIRDRACE Die Wetterauer. 131 records from BIRDRACE Brut. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 1 records from Haslauer Moor. 2 records from Hildener Heide - Spörkelnbruch (Haan). 6 records from Boimstorfer Sundern. 1 records from Karpfenteich, Klasse 6d. 5 records from Fledermäuse u. nachtaktive Insekten. 80 records from Landschaftsschutzgebiet Schmutterwald. 107 records from Müritz-Nationalpark. 359 records from Pöhlberg bei Annaberg. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 366 records from Weinberg Reichersdorf. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 369 records from BIRDRACE Havelland. 269 records from BIRDRACE Kosmos-Racer. 279 records from BIRDRACE Wannacks Topti(c)ker. 65 records from BIRDRACE Federal Birds of Investigation FBI. 140 records from BIRDRACE Guckers Offenbach. 78 records from BIRDRACE leucorhö statt logorrhö. 82 records from BIRDRACE Buteo2DO. 166 records from BIRDRACE Die Düsselmöwen. 96 records from BIRDRACE Emslandracer. 101 records from BIRDRACE Enger am Spektiv. 103 records from BIRDRACE federleser. 104 records from BIRDRACE Erlanger Piepmätzchen. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 114 records from BIRDRACE VIE will rock you!. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 173 records from FFH-Gebiet Klosterwasser/Burkau. 54 records from Königsdorfer Wald. 116 records from Sürther Aue. 88 records from BIRDRACE Kingfisher. 177 records from BIRDRACE Mehr Seh Team. 114 records from BIRDRACE LiLaLau. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 152 records from BIRDRACE NAJU-Aspach. 40 records from BUND Naturschutzzentrum St. Julian. 38 records from Was lebt in der Brutzwiese?. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 11 records
Keywords: GBIF; biodiversity; species occurrences